Pertumbuhan Dan Pembangunan Ekonomi - Sarahfina; Selvi Irene Claudia; Riskia Ramadhani; Nur Fitriana (Jurnal Ekonomi dan Bisnis Digital, 2024)
Macroeconomics has two basic ideas: economic development and growth. The growth of Gross Domestic Product (GDP), which represents the entire production of a country, is a leading indicator of economic growth. On the other hand, economic development covers more areas, including improving people's living standards, their quality of life, and their general well-being. This study explores the differences between economic growth and development, the factors that influence them, as well as the impact of economic policies on both concepts. Analysis of the literature shows that sustainable economic growth can improve the quality of life, but inclusive economic development requires policies that support fairer distribution, better access to basic services, and Community Empowerment. Policy recommendations to promote inclusive and sustainable economic development are also presented in this study.